Changes of Routine Hematological Parameters in COVID-19 Patients: Correlation with Imaging Findings, RT-PCR and Outcome - Abdolreza Javadi; Shahriar Dabiri; Manzumeh Shamsi Meymandi; Mohammad Hashemi-Bahremani; Hussein Soleimantabar; Bahram Dabiri; Houman Vosough; Maryam Gheidi Sharan; Farnoosh Sedaghati (Iranian Society of Pathology, 2022)
Background & Objective: Coronavirus disease 2019 (COVID-19) is progressively spreading, and many researchers have focused on the prognostic value of laboratory analyses. This study reviewed routine blood parameters, upper respiratory viral load, and chest imaging in recovered and expired COVID-19 patients and evaluated possible correlations.Methods: In this retrograde study, 138 COVID-19 cases were enrolled. Chest tomography scores of patients, routine hematologic and  biochemical parameters, and respiratory viral loads were measured. Furthermore, their correlation with severity of disease  and the outcome was investigated during a week of admission.Results: The mean age of participants was 58.6±16;  36.2% of whom were diagnosed as critical, 8.7% expired, and 46% showed less than 50% lung opacity. The expiring rate was only correlated to the severity of illness and viral load. During admission, hemoglobin concentration was decreased in critical patients (from 11.49±0.27 to 10.59±0.36, P=0.042) and also among CT-scan scoring groups (P=0.000), while neutrophils (P=0.04), WBC (P=0.03), and platelets (P=0.000) count were increased. In patients with more than 50% lung opacity, leukocyte counts were decreased, but neutrophil and platelets counts showed raise (all P<0.05), while other hematologic parameters did not change. CRP and LDH demonstrated no  increase based on the severity of the illness, RT-PCR viral loads and/or outcome. However, both CRP and LDH were increased in patients with more than 50% lobal opacity (CRP: 69.3±9.9 to 1021.1±7.5 and LDH:589.5±93.2 to 1128.6±15.81, P<0.05).Conclusion: We found that hemoglobin, white blood cells, neutrophil, lymphocytes, and platelets count together with chest tomography score might be beneficial for expedition the  diagnosis, assessmen the severity of the disease, and outcome in the hospitalized cases, while CRP and LDH might be considered as the consequence of lung involvement.